Integrating authentic learning practice to develop problem solving competency in learning electrolysis - Muhamad, S. (American Scientific Publishers, 2017)
This paper discussed the integration of authentic learning practice to develop problem solving competency (PSC) in learning electrolysis. Global education in this 21st century is crucial to generate the critical and competent problem solver. Then, it becomes a new challenge to provide the authentic learning environment with a comprehensive module to facilitate students to solve non-routine problems that are related to their real lives. PSC in learning chemistry is a partial application of higher order thinking skills (HOTS) to solve the real life problems. In this present study, a module was developed by authors to evaluate the impact of authentic learning practice on the chemistry problem-solving competency among secondary school students. It utilised the quantitative method and involved 46 students studying chemistry at a boarding secondary school in Sarawak. The intervention program consisted of authentic practices in teaching and learning electrolysis by using the newly developed module of authentic chemistry problem solving competency (MAC-PSC). The participants were assigned to solve real life tasks during the intervention to develop their problem-solving competency. Pre and post-tests were administered to determine their performance in solving the open-ended problem regarding electrolysis. The finding revealed a significant difference at α = 0.05 between the participants’ tests mean scores before and after use of the module. It has given a positive effect on the average level gain of understanding in learning electrolysis. Outcomes from this study indicated a significant positive impact on the implementation of the newly developed module in enhancing the HOTS among school students.